STRATEGI PERSIAPAN PENGAJUAN IJIN OPERASIONAL DI TPA BRIGHT MINDS SALATIGA - Catharina Leksananingtyas; Lanny Wijayaningsih (Satya Widya, 2018)
ABSTRACT The objective of thisresearch is to find out about the operational requirements of a Daycare Center (TPA) in order to help the TPA Bright Minds Salatiga getting its operational permit. The nature of this research is descriptive qualitative. Subjects of the study are the TPA Bright Minds Management and the Caregivers. Data is collected using observations, documentations, and deep interview methods. The collected data isanalyzed using techniques of data reduction, data presentation and verification. The results showed that there are two main categories of operational requirements, i.e. adminstrative and technical requirements. The administrative requirements include submision of TPA founder identity, certificate of domicile from the local headman, structure and detailed role of each of the Board members. The technical requirements are legal and valid documents of ownership/leasing rights of the land and buildings, estimated operational costs of the TPA, plan of TPA implementation standards, and some other additional documents. Thus, based on study's results, it is to suggest that the TPA Bright Minds Salatiga, should immediately strategize an application of its operational permit to the authorities.